The Existence of Pancasila in Post-Truth Era - Ayon Diniyanto; Wahyudi Sutrisno (Badan Pembinaan Ideologi Pancasila, 2022)
The existence of Pancasila must be maintained. The post-truth era that is already in sight can certainly have a negative impact on national identity. Pancasila as the identity of the Indonesian nation must be maintained and become a bulwark against the negative impacts of the post-truth era. The writing of this article is very important in providing an understanding to the Indonesian people that the post-truth era cannot be avoided. As a nation that has an identity called Pancasila, Pancasila should be implemented in the life of the nation and state, especially in the face of the post-truth era. This is where the importance of this article in reminding about the negative impact of the post-truth era on national identity. This article discusses three important issues related to Pancasila and post-truth. These three things are (1) various kinds of negative impacts that can or even have been caused by the post-truth era; (2) finding the relevance of the post-truth era with Pancasila; and (3) describes how to maintain the existence of Pancasila in the vortex of the post-truth era. There are at least three negative impacts of the post-truth era, namely (a) the existence of lies; (b) the existence of slander; and (c) the presence of hate speech. The relevance of the post-truth era with Pancasila lies in the identity of the nation. The post-truth era can have a negative impact on national identity. Pancasila is the identity of the Indonesian nation. The existence of Pancasila in the post-truth era must of course be maintained so that it is not negated by the negative impacts of the post-truth era. The way to maintain the existence of Pancasila in the post-truth era is to apply Pancasila in the life of the nation and state and to strengthen literacy. The conclusion of this article is to answer the problem formulation and find the purpose of this article.